Stay close [compact disc, unabridged] - Coben, Harlan, 1962- (Brilliance Audio, 2012)
Three people living lives they never wanted, hiding secrets that even those closest to them would never suspect, will find that the past doesn't recede. Even as the terrible consequences of long-ago events crash together in the present and threaten to ruin lives, they will come to the startling realization that they may not want to forget the past at all.